Polish Palaeobotany: 750 Million Years of Plant History as Revealed in a Century of Studies. Palaeozoic Microflora - Maria Barbacka; Grzegorz Pacyna (Acta Societatis Botanicorum Poloniae, 2022)
All the palynological studies of the Polish Paleozoic were conducted during the last 100 years. The investigations regarded the oldest microflora remains, acritarchs reaching up to Precambrian, and spores, and pollen grains which appeared later. The main benefits of palynological analyses are their stratigraphic significance, usage for age determination, correlation of stratigraphic horizons, detection of climatic changes, and information on plant cover, often providing supplementary data for macroflora records. The most important results of Polish palynology demonstrate the multifaceted character of studies and their significance in science.